Enhanced electromagnetic interference shielding performance of geopolymer nanocomposites by incorporating carbon nanotubes with controllable silica shell. Issue 8 (15th April 2022) - Zhu, Yuping; Bai, Ben; Ding, Enjie; Bi, Shuguang; Liu, Wanshuang; Zhang, Liying
Abstract: The development of construction materials with exceptional electromagnetic interference (EMI) shielding performance is urgently needed to restrict the admittance of electromagnetic (EM) radiation. In this work, silica (SiO2 )-coated carbon nanotubes (S-CNT) with different shell thicknesses (∼7, ∼10, and ∼15 nm) were prepared by a sol-gel method. The effect of SiO2 shell thickness on the EMI shielding performance of the resulting geopolymer nanocomposites was studied. The coated SiO2 shell effectively facilitated the dispersion of CNT in the geopolymer matrix due to the chemical reaction between SiO2 and the geopolymer. The dispersability of modified CNT could be further improved by increasing the thickness of the SiO2 shell. However, electron delocalization was hindered by the insulating SiO2 shell. The conductive nature of CNT was restored during geopolymerization when the SiO2 shell was thin. A high EMI shielding effectiveness (SE) of 24.2 dB was achieved for the geopolymer nanocomposite containing 5 vol% S-CNT with a thin SiO2 shell. The value achieved was more competitive than reported composites for construction when the sample thickness and filler content were considered.